USING CONVOLUTIONAL NEURAL NETWORKS FOR BREAST IMAGING AND TO MO SYNTHESIS CATEGORIZATION - Lakhendra Kumar (International Journal of Multidisciplinary Research and Studies, 2020)
In the United States, 99 out of every 100 people diagnosed with breast cancer are women. About 12 percent of all girls in the United States may be diagnosed with breast cancer sooner or later in their lives. Currently, breast cancer is the type of aggressive cancer that most often affects women. This mortality rate related to breast cancer has been shown to have a preferred declining trend over the past several decades. But, because of the large number of breast cancer diagnoses each year, about 40,000 people in the United States die as an immediate result of the disease. When cancer is detected in the early stages, cancer cells are most likely to be located in a localized part of the body. As a result, it is easier to control the disease when the right medicinal drug is introduced. While cancer cells spread to other areas of the frame, it is far more difficult to deal with and subsequently treat the disorder.